2022
DOI: 10.1152/japplphysiol.00688.2021
|View full text |Cite
|
Sign up to set email alerts
|

Power attenuation from restricting range of motion is minimized in subjects with fast RTD and following isometric training

Abstract: Time-dependent measures consisting of rate of torque development (RTD), rate of velocity development (RVD), and rate of neuromuscular activation can be used to evaluate explosive muscular performance, which becomes critical when performing movements throughout limited ranges of motion (ROM). Using a HUMAC NORM dynamometer, seven males (27 ± 7 years) and six females (22 ± 3 years) underwent 8 weeks of maximal isometric dorsiflexion training 3 days/week. One leg was trained at 0° (short-muscle tendon unit (MTU) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the ankle plantar flexors, Beck et al (2021, preprint) observed lower metabolic costs of cyclic force production in longer compared to shorter fascicle operating lengths under the same mechanical work and shortening velocity. Hinks et al (2020) and Davidson et al (2022) observed a 4% increase in tibialis anterior FL following 8 weeks of isometric training at a long muscle-tendon unit length, and an 11% increase in work of shortening, and 25% and 33% increases in isotonic power at loads of 10% and 50% maximum, respectively. However, they also observed increased isometric strength, pennation angle, and muscle thickness, so we can only speculate that those improvements in work and power were due to increased FL rather than strength and hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the ankle plantar flexors, Beck et al (2021, preprint) observed lower metabolic costs of cyclic force production in longer compared to shorter fascicle operating lengths under the same mechanical work and shortening velocity. Hinks et al (2020) and Davidson et al (2022) observed a 4% increase in tibialis anterior FL following 8 weeks of isometric training at a long muscle-tendon unit length, and an 11% increase in work of shortening, and 25% and 33% increases in isotonic power at loads of 10% and 50% maximum, respectively. However, they also observed increased isometric strength, pennation angle, and muscle thickness, so we can only speculate that those improvements in work and power were due to increased FL rather than strength and hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
“…In the ankle plantar flexors,Beck et al (2021, preprint) observed lower metabolic costs of cyclic force production in longer compared to shorter fascicle operating lengths under the same mechanical work and shortening velocity Hinks et al (2020). andDavidson et al (2022)…”
mentioning
confidence: 99%
“…In support of this, using a similar fatiguing task in the plantar flexors but assessing velocity and dynamic torque with an "unloaded" (weight of dynamometer arm only) contraction, we previously reported that impairments in power were more due to velocity than dynamic torque (30). Thus, the contributions of dynamic torque and velocity for reductions in power generating capacity after the fatiguing task are load dependent but likely depend on various related factors, including the muscle group evaluated and the ROM used in the task (10). Shortening-induced residual force depression is a deficit in isometric torque output after a loaded shortening contraction (31), which may be larger for slower contractions (i.e., higher loads) and for a greater shortening ROM (32).…”
Section: Discussionmentioning
confidence: 99%
“…Applying these approaches to dynamic contractions can be challenging because of the nonsteady-state nature of these contractions, especially during isotonic-like contractions (defined here as a dynamic contraction using a constant load) that may achieve full range of motion (ROM) in short timeframes (e.g., <0.5 s). Because of this time-dependent nature of isotonic contractions, the rate of velocity development (RVD, i.e., acceleration) is a key factor for achieving peak power output (9,10); however, these factors may be dependent on the load used for the dynamic contraction (11).…”
mentioning
confidence: 99%